TUTURAN PERSUASIF MARIO TEGUH DALAM ACARA MARIO TEGUH GOLDEN WAYS DI METRO TV: ANALISIS PRAGMATIK - Kharisma Thahira; Charlina '; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This research aims to describe of the shape persuasive speech and persuasive techniques by Mario Teguh used in the program Mario Teguh Golden Ways on Metro TV. This research is use qualitative study methods with a descriptive approach. Objects in this research is persuasive speech by Mario Teguh. Technique of data collection is done by using see-note technique and documentation of three-run episodes Mario Teguh Golden Ways. Results of this research of classification shape a persuasive speech and persuasive techniques by Mario Teguh in the program Mario Teguh Golden Ways on Metro TV. Based on the data analysis found that the shape used persuasive speech by Mario Teguh are: (1) assertive, (2) directive, (3) commisive, (4) expressive, and (5) the declaration, while persuasive techniques used are: (1) the association, (2) integration, (3) pay of, (4) fear hearing, (5) red-herring, (6) seetings.Keys words: persuasive speech, shape of persuasive, persuasive techniques.